Novel Cellulose Acetate-Based Monophasic Hybrid Membranes for Improved Blood Purification Devices: Characterization under Dynamic Conditions - Adriana Janeca (MDPI AG, 2021)
A novel cellulose acetate-based monophasic hybrid skinned amine-functionalized CA-SiO2-(CH2)3NH2 membrane was synthesized using an innovative method which combines the phase inversion and sol-gel techniques. Morphological characterization was performed by scanning electron microscopy (SEM), and the chemical composition was analyzed by Fourier transform infrared spectroscopy in attenuated total reflection mode (ATR-FTIR). The characterization of the monophasic hybrid CA-SiO2-(CH2)3NH2 membrane in terms of permeation properties was carried out in an in-house-built single hemodialysis membrane module (SHDMM) under dynamic conditions. Permeation experiments were performed to determine the hydraulic permeability (Lp), molecular weight cut-off (MWCO) and the rejection coefficients to urea, creatinine, uric acid, and albumin. SEM confirmed the existence of a very thin (<1 µm) top dense layer and a much thicker bottom porous surface, and ATR-FTIR showed the main bands belonging to the CA-based membranes. Permeation studies revealed that the Lp and MWCO of the CA-SiO2-(CH2)3NH2 membrane were 66.61 kg·h−1·m−2·bar−1 and 24.5 kDa, respectively, and that the Lp was 1.8 times higher compared to a pure CA membrane. Furthermore, the CA-SiO2-(CH2)3NH2 membrane fully permeated urea, creatinine, and uric acid while completely retaining albumin. Long-term filtration studies of albumin solutions indicated that fouling does not occur at the surface of the CA-SiO2-(CH2)3NH2 membrane.